Neograeca Medii Aevi VII - Rosemary E. Bancroft Marcus.wmv (Ιστορικό Μουσείο Κρήτης, 2013)
: Ο τίτλος της ανακοίνωσής μου είναι κάπως δύσκολονόητος. Θα σας μιλήσω μισό αγγλικά και μισό ελληνικά, δεν πρόλαβα να μεταφράσω ολόκληρη την ομιλία μου στα ελληνικά, αλλά θα έχω αποσπάσματα και παραδείγματα να σας διαβάσω. Φτάσαμε στην Κρήτη τη Δευτέρα, εγώ και ο άντρας μου, ύστερα από μια πολύχρονη αποσία. Ανυπομονούσα να ακούσω πάλι την ωραία κρήτικη προφορά. Την Τρίτη το αποήβμα, είμαστε σε ένα καφενείο κοντά στα λιοντάρια και είδαμε ένα σωρό από πουλάκια που κατέβαιναν, ταιρετίζοντας, να περάσουν τη νύχτα σε ένα τέντρο. Ρώτησα τον σερβιτόρο ποια πουλιά ήτανε και αυτός μου απάντησε πολύ ευγενικά, είναι σπουργίτσια, κυρία μου. Χάρηκα τόσο πολύ να ξέρω πως η παλιά κρήτικη ομιλία διασώζεται ακόμα στις μέρες μας και ελπίζω και παρακαλώ να μην εξαφανιστεί ποτέ. Το ήχος, το φωνήτικο στοχείο μιας γλώσσης είναι ικανό εξαρτώντας από τα συμφραζόμενα να δίνει ευχαρίστηση στον ακροατή. Ένας κρήτικος του 16ου αιώνας που γεννήθηκε στα Χανιά και που έκανε λαμπρή καριέρα στη Βενετία σαν βιβλιοτικάριος, η συμμαρχιανή ο Αμβρόσιος Γραδενίγος αγαπούσε πολύ τη διάλεκτο της γενέτειράς του. Στην έκδοση του που έκανε της αεροφύδης της γνωστής τραγωδίας του Γεωργίου Χωτάτση, η επιστολή με τίτλο «Είσθους αναγινώσκοντας ο τυπογράφος» εκφράζει κατά την νόμιμου την αηδία που προκάλεσε στον ίδιο το Γραδενίγο, η πρώτη άσχημη εκδοσία της αεροφύδης του Ματέο Κηγάλα. Αξίζει τον τόπο να διαβάσω αυτό το γράμμα, γιατί δείχνει με σαφήνια και δύναμη σε ποιό βαθμό οι Κριτικοί της εποχής, που ένιωθε την ανάγκη να προστατεύουν τη διάλεκτό τους. Λέει «Η παρούσα τραγουδία, όσον είναι μελήρητος και γλυκοδυγίγητος εις την φυσικήν της γλώσσαν την Κριτικήν, τόσον είναι ανωστομίλητη και σιχαδερή εις η τέραν και άλλοδαπήν ομιλίαν. Επειδή λοιπόν η τυπόθη πρόπαλλε εις γλώσσα κατά πολλά διαφορμένην, όπου καμία νοστιμάδα δεν επροξένα, μάλιστα ναφτιασμών και αναγουλιασμών επαρακοίνα εις όλους, ειδού όπου τώρα ναιωστεί με επιμέλιαν και έξοδον εδικίνου, την δίδομαι εις τον τόπο». Είναι ο τυπογραφός εκεί που γράφει, νομίζω πως ο γραδινήγος κάτι έβαλε μέσα. «Προς χάριν των αναγνωσκών διορθωμένην ως εγγράφη και εν εσυνδέθη από τα σχεράς του πίτου. Όλοι κοινός οι φιλομαθείς θέλουσι την αγοράσι με τα καράς, αλλά εξαιρέτως οι κριτικοί, και πάντες ομοθημαδών θέλουσι χαίρονται εις την ευρυθμίαν των στίχων. Κι αν κανείς δεν ευχαριστάται εις κάποια λόγια και λέξεις κριτικές, ως αν όπου δεν είναι του κανόνως, ή της εγχωρίου του ομιλίας, ας πασχύσει να θα συνθέσει κι αυτός πίημα μερικών της ορέξιος του, κι όχι να νοθεύει το φυσικών και γνήσιων ιδίωμα του παρόντος πιήματος με ατιμία του πίτου, όπου αιστάθη εις τούτο το γένος ο κορυφαίος των πίτων. Πάσα γλώσσα χαίρεται εις τους ιδιωματισμούς τους ιδίους, κι αν κανείς μην οπωκοτά ποτέ προπετός να συγχύζει τας γλώσσας, ερώσθε. Υπάρχουν επαγγελματικές ελληνικές γραμμές του Πανόρια, Εροφίλου, Κατσούρβου, Σταθίου, και των 14 εντελείων μεταξύ αυτών των γραμματικών. Ακόμα και 9 που είναι το έργο του Χοτάτιου και τα άλλα είναι μέρος της θεατρικής παραδοσιακής του. Οι γραμματικές γραμματικές ελληνικές γραμματικές ελληνικές γραμματικές ελληνικές ελληνικές γραμματικές γραμματικές σ️ ίδιωνowane κίνητρο βασιλ homage συλλ passé understand δεν็ είναι ενδιαφέρον μικ aha προς την ελληνική υφελ fences Στο δεύτερο βιβλίο του βιβλίου, δημιουργημένος ως συμπανιώτης στον πρώτο βιβλίο, προσφέρουμε μια πλήρη παραδοσιασμή, δημιουργημένη, απελευθέρωσης, κριτικός και γλώσσα. Αυτό, επίσης, θα πηγαίνει σε 600 βιβλίων. Αυτό είναι το 656 βιβλίων. Ελπίζω να συνεχίσω το δεύτερο βιβλίο το επόμενο πρωτοβουλί, για να δημιουργηθώ όσο κοντά στον πρώτο βιβλίο, ώστε να μην πρέπει να περιμένουμε πολύ λίγο για τους κριτικούς απελευθέρωτες. Αυτό το δεύτερο βιβλίο ασφαλίζει μια σημαντική σημασία. Η πραγματικότητα είναι ότι η λιτουργία της Κρήτης και της Ρενεσσόνιας ήταν μια πραγματική ορλή μορφή, χαμηλώντας μεταξύ της φωκσάγκας και της δημιουργίας. Βιβλία σχηματισμένη για τη δημιουργία ή της παραδοσιασμής. Η εντυπωσία της υποστηρίζεται από την ακούγονση. Μετά από αυτήν την εποχή, ακόμα και οι μηχανικοί δημιουργοί έκανε δημιουργητικά. Οι πραγματικοί έκανε συχνά μέσα στην οικογένεια ή πριν από την οικογένεια, και η δραματική διαλόγη ήταν ενδιαφέροντα για τους δημιουργούς που όλοι οι δεύτεροι ήταν ασφαλισμένοι σε κάθε μορφή εμφάνισης, ακόμα και όταν οι δεύτεροι έκανε δημιουργητικά με τις δημιουργικές σχέσεις της ζωής. Η υπέροχη ακόμα και μερικών λατίνικων μανιστρικών, αν είναι αυτογράφης ή κόπη, των δημιουργικών δημιουργικών δημιουργικών δημιουργικών δημιουργικών δημιουργικών είναι πολύ αξιοπρέπειτο. Είναι έναν δημιουργικό σχόλιο σχόλου και μετρικών πρακτικών. Έχουμε μια πιο ακόμα γνωστή γνώση για πώς ήταν δημιουργηθεί αυτά τα τεχνικά δημιουργία από την δημιουργία του Shakespeare. Το δημιουργικό της Κρήτης είχε σε αυτή τη στιγμή έναν σχετικό σπαντιστικό σχόλιο, με το ήχο «ι» ή «ιε» σχετικά με το «λ» και το «ν» πριν τις δημιουργίες «ι» και «ε». Για να σας δείξω τι σημαίνει, θα προσπαθήσω να διαβάζω λατίνικα μορφή από το «Λεγκρον» μανιστρικό, τώρα στην Αθήνα, από το «Ροζ» μανιστρικό, από το δεύτερο από τους εντυπωσιακούς εντυπωσιακούς στο «Ερροφύρι» πρόγραμμα 1 και 2. Όπως μπορείτε να γνωρίζετε, αυτό βασίζεται από ένα πρόγραμμα από τον Τάσος «Γερουσέλεμι Λιβράτα», όπου το μανιστρικό πρόγραμμα είναι δημιουργηθεί από ένα εντυπωσιακό, πολλογραφικό παράδικο. Δεν έχουμε κανείς ιδέα τι τέτοιο τραγούδι έπαιξε το μανιστρικό στον Κουρτάσις. Λοιπόν, δέτε το ρόδο το ταχύ πως δρόσερο να αρχίζει να φαίνεται στα γκάθη του και να μοσκομυρίζει. Κι όμορφο δίκτη στο κομπί, για μάλαγο περίσα, σαν ένα ευγενικότατο μικρό κοράσανίσα. Κι όσον η μέρα κλειότερα προς το βραδί συμμώνει, φουτώνουσι τα φύλλα του και ανοίγει και ξαπιώνει. Κι αγάλια αγάλια ψήγεται και τη θοριά του χάνει κι αγαπτικός δεν το ψηφά, κοράσαν δεν το πιάνει. Έτσι και τάθη σφύνουσι τη νιώτης και χαλούσι και να ξανεγρύζουσι τσι ανθρώπους δεν μπορούσι. Λοιπόν, το ρόδο πάσα μιας μέρας, πριν ορθεί το βράδυ, το μυρισμένο βιάζεσθαι να πιάνεται όλη η ομάδη. Πιάστε το ρόδο τσι φιλιάς, κι αγαπτική λογάσθαι, όνοι αγαπώντες πιστικά κι εσείς μπορά αγαπάσθε. I've turned this into English thus just to give you an idea. See how the dewy rose begins at dawn to open on her thorny stem, musk perfumed. How beautiful the bud appears, as pure as the most delicate of little maidens. But as the day draws further on to dusk, her petals spread, she opens out, grows blousy. Then bit by bit she withers, beauty lost, and lovers scorn her, maidens will not pick her. So too the bloom of youth fades out and spoils, and once it's gone no human can regain it. Therefore be prompt to pluck the scented rose of every day before the evening's onset. Gather love's rose, enroll as lovers while you still, when loving faithfully, may be loved. If you look at the Latin script passage there, you'll see some characteristics of Latin script composition. There are no accents. In some manuscripts we find an occasional final syllable grave. So it's remarkably uncluttered, this text. It's neat, economical, and easy to transcribe. There's no worry about classical spelling. There's no worry about where the accents go. The clitic pronouns are attached to their governing nouns, verbs, adjectives, and adverbs without intervening space. So you've got an example of that. Everything is attached as if it was one word. The nasal n combines in some circumstances with the following unvoiced p or t which unconverts them into a voiced g, b, d. So the sound of delta is written th with d-h, whereas the sound of d is represented just by a single d. And that we would write in Greek script as new, tough, neat, tough. Even if we write final new on any word before any other consonant than those, it's actually wrong. And I've often seen that on the verb to be, in, followed by other consonants than the ones that can nasalize. Final new is placed between vowels to avoid hiatus in the verse of Horchatsis, Cornaros, and Troilas. A gap between vowels, hiatus, is only permitted at the caesura and is quite rare in the two Ruthenian playwrights. Final i, iota, may stand for either the vowel i or the sound y. The latter is a semi-consonant and as such it cannot logically be accented. So here in this passage we have prierti tovoradi. It isn't pri at all, it's pri. It's very difficult to say, but prierti, like that. And this has to be taken into account, but we find it very odd. And quite often in a standard edition we might find that whole thing written out as l'hypothorodo pasa mias meras, prierti tovoradi. And that would spoil the beat. Prierti is correct. The sound of iot, as I've said before, intervenes between n and ie and l and ie. It's a bit like Spanish mañana. Accent position is given to the reader of Hotates' day by meter. They knew that it was basically a fluctuation of weak and strong syllables, sometimes with strong syllables at the beginning of each hemi-stick for particular emphasis. They knew that the iambic decapenda syllable falls into two rough halves. They worked out where the break was and they fitted in the beats from their own knowledge of their language. And that's actually rather more difficult for us and especially for foreigners. Accent position is not indicated by written accent and the consequence of that is that it might be flexible. In this very passage you have vradi in one place and vradi in another in the space of a couple of lines. And that also might be obscured by rather conventional accentuation in a modern edition. Adjoining vowels, meaning final and initial vowels of two words within the hemi-stick, were meant to be pronounced in synaesthesis, merging to form a single metrical syllable. And it's actually a fault to read them as if they're separate. The first vowel often yields to the second and in Greek script editions, the Venetian ones, we often find that the first vowel is actually elided. But in Latin script manuscripts we find them both written out. Synaesthesis may involve pairs of like or unlike vowels, whether accented or unaccented. And there are some cases of difficult synaesthesis where you find that both vowels in a traditional or conventional edition ought to be written with accent, but in fact only one of them carries the accent and it's usually the second. An initial a falling on an even numbered syllable, that's the beat of the meter, is often felt or treated as if accented, even though the formal accent of the word may be two or more syllables distant. And I don't really see why the Cretans should have worried about where the formal accent was. They wrote it as they spoke. And although some people like Peter Makaritch disputes the existence of a secondary accent, but I think when you are talking about metrical texts, secondary accent is quite important. So you may actually get quite a strong accent on an initial alpha, even though the formal accent is two syllables later. Now in Greek script composition words are more separated, but not entirely. We still find that clitics are attached. And in my own edition I've actually connected them with a hyphen. It makes things so much easier because you don't then have to worry about direct and indirect objects. You see exactly where they belong. In Greek script texts we find a lot of elision and prodilision with loads of apostrophes. The gradenigos even indicates the absence of optional initials, bearing in mind his early memories of, well I'm sure he still spoke Cretan Greek, forms like oligora, eligos, oia, that kind of thing. In Greek script texts of the middle 17th century find that synaesthesis is reduced, especially of unlike vowels. Usually the final vowel is knocked out, even or perhaps especially when conventionally accented, because they didn't actually want to have the reader struggling to do two accents at once on one metrical syllable. Accents are imposed according to rules in Greek script texts, according to rules derived from classical texts, which may not necessarily match the natural or flexible accent positions in Cretan Renaissance Greek. If you have a look at the passages three and four on the back of your handout, these are from the gradenigos 1676 edition of Erophile, and you will see there some rather strange phenomenon. Instead of saying writing tin tragodia axiopiima, and I don't know how many syllables that makes, he says we should read tin tragodiaxopiima, it's actually axo in the proper dialect form. So he's telling us that there are not two metrical syllables there, tin tragodiaxopiima. There's four, but not tin tragodiaxopiima, which makes many more. And in the line below, he's saying that instead of saying navioxopiima, which is really three words, we should say navioxopiima, like that, all together. And it's quite difficult for us to accommodate that. In the passage below, there's quite an interesting example, that clump. And you will see that that is composed of ke, esteke, because it's third person singular, the subject is nous. And we're supposed to read that, according to gradenigos, as keste kiarifnito kero. So the last epsilon of esteke turns into a y sound before the following a. We cannot expect poets using a phonetic writing system so closely based on spoken vernacular to follow rules laid down for Greek script texts associated with other times, places, and registers. And we need to remain open-minded about the possibility that an accent position that looks quite wrong, because it differs from accent or modern Greek and is not attested by even the modern Cretan dialect, may in fact have been natural and right in 16th century Cretan. Our best evidence for accent placing is meter. Meter is paramount. If a particular word appears to conflict with the normal rhythm over and over again in a variety of texts, with no stylistic justification for such a jarring effect, we have to ask ourselves whether it is correctly accented. The word ekki, for example, may sometimes be accented ekki. And those who doubt that should think of the word parekki and apekki. The word anisos may sometimes be pronounced anisosh. We find iati, oyati, and oyati coexisting within a page or two of the same text. And that shouldn't surprise us. Flexible accent position is not a poetic artificiality, but a reflection of natural Cretan speech habits drawn from the main dialectal regions of East, Central, and West. From the towns and from survivals of older forms of speech, like pleia instead of pia, vasileas and vasilias, which provided the poets with a range of alternative morphologies and rhyme words. But Venetian printers, and we in our own day, add accent to syllables on the basis of classical accent position and what we know or can find out about contemporary Greek. The Venetian printers were not especially concerned with making sure that accent fell on metrically strong syllables. They sought a convenient rule to follow for all words similarly spelt, even though certain words, particularly dis-syllables, are sometimes in their metrical context pronounced in different ways. Examples are tone, choris, and oia, which may be accented on the first or second syllable or not accented at all, depending on their position within the line and their relationship with the surrounding words. The phrase ventone, normally pronounced and written as ventone, may sometimes be pronounced in the middle of the hemostic in enclitic fashion as ventone, and I've also seen cases of natone behaving in a similar way. Kouratinikos' innovations are really very interesting. In some cases, he actually makes spelling a little simpler to indicate that the sound u is meant to be in that place. For example, he puts words together which we would separate, for example, iatioso, and I've heard a lot of people saying today when they've been reading out their passages they would read it as iatioso, but iatioso is the way it should be, and he writes that as one word without an intervening gap. Sometimes in iati he leaves the final iota unaccented, and in my own texts I have left it without accent when it's followed by a vowel with which it is in synesthesis. In my texts I've used what I call a phonotonic accent system, which is a development of the monotonic. A lot of people now are beginning to use the monotonic for texts of this period. The difficulty with that is, and it's obviously a great simplification for printing and all the rest of it, the difficulty is that it imposes no accent on monosyllables, and there's a ton of monosyllables in the Cretan dialect which are very strongly accented in their metrical context. So to leave them off, it removes the peaks. Every line has a kind of peak of emphasis, and if we take those accents away we read it rather flat, like a kind of French monotone, and I think it would be better to put the accents in on such words like yis meaning land, earth, and fos meaning light, and all that sort of thing. It's not a very difficult change to make, just to make sure that accent comes where there is pronounced stress, and it helps a great deal with scansion. These works really are meant to be read aloud, and all of us should practice reading them aloud. One thing that would actually help quite a lot, particularly in Tochothrothormos, is when there's huge long words, each of which occupies one hemi-stick, I think we could do with a second accent at the beginning of the word, and not wait right to the very end before we know where to start. It's extremely difficult to know how to start the word off if we don't get some clue in the first quarter of the line, and with compounds there's quite a lot of justification for putting in a second accent. It makes things clearer. How much time have I got left? Finish? Yes. That is basically what I wanted to say.